Jedrska ura - Jurkovič, Jan (Matrika, 2018)
As time precision becomes more and more useful and important, new ways of time measurement have been born. Today's most precise time and frequency measurements are performed with atomic clocks. The most precise ones work so well, that if they worked for tens of billions of years, they would be less than a second off. However, in the future they could be even outperformed by the so-called nuclear clocks. While the atomic clock is based on the excitation of the electrons in an atom, the nuclear clock would work with excitation of an atomic nucleus, which is promising, because the atomic nucleus is less affected by the effects of the surroundings like the electrons in the atomic shell. For an atomic clock, atoms of different elements can be used, however the nuclear clock could be based only on one of the known 176.000 nuclear levels on the first excited nuclear state of 229Th. But to actually build a working nuclear clock there is still so much left to discover.
Keywords: atomic clock; atomska ura; jedrska fizika; jedrska ura; merjenje časa; nuclear clock; nuclear physics; time measurement